The effectiveness of written peer feedback in improving writing skills as perceived by second-year students at FELTE, ULIS-VNU = sự hiệu quả của phản hồi đồng đẳng dạng viết trong việc trau dồi kỹ năng viết dưới nhận thức của sinh viên năm hai khoa sư phạm tiếng Anh Trường Đại học Ngoại ngữ - Đại học quốc gia Hà Nội - Nguyễn, Thị Thanh Huyền (2020)
The present research attempts to determine the effectiveness of written peer feedback in improving writing skills, particularly in some certain aspects of writings namely organization of ideas, content, grammar, vocabulary and mechanic use as perceived by second-year students at FELTE, ULIS-VNU. Besides investigating the ways written peer feedback helps students improve writing skills and examining the extent of its effectiveness in promoting writing proficiency, the paper puts forward the plausible solutions to boost the effectiveness of written peer feedback application remarkably. For the sake of achieving these significant goals, both quantitative and qualitative research method are implemented. First, the survey questionnaire is distributed to participants in order to obtain an in-depth investigation into their perception towards the effectiveness of written peer feedback in improving writing skills and the feasible solutions to promote the efficiency of written peer feedback. Second, with the aim of determining the effectiveness of written peer feedback in improving writing skills, writing analysis from students’ writing assignments is carried out rigorously. Third, in-depth interviews are undertaken to enhance the reliability and sharpen the findings of the study. The results of the research have revealed that written peer feedback plays a pivotal role in improving writing skills, albeit by varying ways and degrees in each aspect.